2013
DOI: 10.3390/molecules18077977
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Herbicidal Activity of Ring-Substituted 3-Hydroxynaphthalene-2-carboxanilides

Abstract: Abstract:In this study, a series of twenty-two ring-substituted 3-hydroxy-Nphenylnaphthalene-2-carboxanilides were prepared and characterized. The compounds were tested for their activity related to inhibition of photosynthetic electron transport (PET) in spinach (Spinacia oleracea L.) chloroplasts. Primary in vitro screening of the synthesized compounds was also performed against four Staphylococcus strains and against two mycobacterial species. 3-Hydroxy-N-(2-methoxyphenyl)naphthalene-2-carboxamide showed OP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
103
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(117 citation statements)
references
References 45 publications
5
103
0
Order By: Relevance
“…Microwave-assisted synthesis [17,18,20] facilitated the process of obtaining ring-substituted 8-hydroxyquinoline-2-carboxanilides, thus synthesis of the target compounds was carried out only by one step. At first the carboxyl group was activated with phosphorus trichloride.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Microwave-assisted synthesis [17,18,20] facilitated the process of obtaining ring-substituted 8-hydroxyquinoline-2-carboxanilides, thus synthesis of the target compounds was carried out only by one step. At first the carboxyl group was activated with phosphorus trichloride.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, according to the results reported recently, some quinoline derivatives and their analogues/isosteres also showed noteworthy herbicidal activities [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Although at present approximately 20 mechanisms of action of herbicides are known [21], over 50% of commercially available herbicides act by reversible binding to photosystem II (PS II), a membrane-protein complex in the thylakoid membranes, which catalyses the oxidation of water and the reduction of plastoquinone [22], and thereby inhibit photosynthesis [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Log k, calculated from the capacity factor k, is used as the lipophilicity index converted to log P scale [4]. N-Alkoxy-3-hydroxynaphthalene-2-carboxanilides, N-alkoxy-1-hydroxynaphthalene-2-carboxanilides and N-alkoxy-2-hydroxynaphthalene-1-carboxanilides were recently synthesized and tested for their antibacterial and antimycobacterial activity as well as for their activity related to the inhibition of photosynthetic electron transport (PET) in spinach (Spinacia oleracea L.) chloroplasts [9][10][11][12][13][14]. Since it was found that the lipophilicity of these significantly biologically effective agents determined their activity, in this study hydrolipophilic properties of all three series are investigated.…”
Section: Introductionmentioning
confidence: 99%